KONTEKSTUALISASI HUKUM KEADILAN DALAM QISHAS - Muchsin, Agus (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
This article describes the problem in Qishas contextualisation Justice. Assessment results obtained from the understanding that the term